2023
DOI: 10.3390/w15040820
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Hillslope Vineyard Soil Water Dynamics Using Field Measurements and Numerical Modeling

Abstract: Soil heterogeneities can impact hillslope hydropedological processes (e.g., portioning between infiltration and runoff), creating a need for in-depth knowledge of processes governing water dynamics and redistribution. The presented study was conducted at the SUPREHILL Critical Zone Observatory (CZO) (hillslope vineyard) in 2021. A combination of field investigation (soil sampling and monitoring campaign) and numerical modeling with hydrological simulator HYDRUS-1D was used to explore the water dynamics in conj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…In this case, it is very interesting to see that, in the northwestern part of the footslope, there are the lowest values of bulk density in the first 40 cm depth, and the highest in the deepest parts. On the other two points in the footslope, values of bulk density are totally opposite with depth, as shown by Krevh et al [59]. In the end, the influence of the slope of the vineyard on the surface and subsurface flow should not be neglected, which is from the northwest to southeast (Figure 1), although results from this study indicate that slope does not have a lot of impact on the variability of the soil water content, which corresponds to previous research where it was shown that the retention of soil water on the slope is more influenced by soil properties [5].…”
Section: Isotopic Composition and Water Mixing In The Hillslope Vineyardmentioning
confidence: 51%
See 3 more Smart Citations
“…In this case, it is very interesting to see that, in the northwestern part of the footslope, there are the lowest values of bulk density in the first 40 cm depth, and the highest in the deepest parts. On the other two points in the footslope, values of bulk density are totally opposite with depth, as shown by Krevh et al [59]. In the end, the influence of the slope of the vineyard on the surface and subsurface flow should not be neglected, which is from the northwest to southeast (Figure 1), although results from this study indicate that slope does not have a lot of impact on the variability of the soil water content, which corresponds to previous research where it was shown that the retention of soil water on the slope is more influenced by soil properties [5].…”
Section: Isotopic Composition and Water Mixing In The Hillslope Vineyardmentioning
confidence: 51%
“…Granulometric soil composition analysis was performed according to [57], while organic carbon content (C org ) was determined using sulfochromic oxidation according to [58]. Values of the bulk density have been estimated using HYPROP-FIT for the hilltop, backslope, and footslope for 4 depths (0-20, 20-40, 40-60, and 60-90 cm) and 3 vineyard rows [59], while, for this research, only the average values for depth up to 40 cm have been used. According to the United States Department of Agriculture soil classification system (USDA) [60], soils have been classified as silt loam or silty clay loam for all three depths [55].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Disturbed soil samples were taken across the inter-row area from three positions (hilltop, backslope, and footslope), covering two soil depths (0-30 and 30-60 cm) at each position. This was replicated in three inter-rows to determine soil texture and soil organic carbon (SOC) [43] (Table 1). The texture was determined by combined sieving and sedimentation (ISO 11277:2020), and the organic carbon content by sulfochromic oxidation (ISO 14235:1998).…”
Section: Soil Datamentioning
confidence: 99%